362 Potential survivability of prehospital injury deaths in New Zealand. (20th November 2022) - Kool, Bridget; Davie, Gabrielle; Graaf, Brendan de; Reid, Papaarangi; Branas, Charles; Civil, Ian; Dicker, Bridget; Ameratunga, Shanthi
Abstract : Background: Most injury-related deaths occur in the first 24 hours following the event. Some of these patients could survive if identified and managed promptly and effectively. Aims: To assess the survivability of prehospital injury deaths in New Zealand. Methods: A cross-sectional review of prehospital injury death post-mortems (PM) during 2009–2012 was conducted. Deaths without physical injuries, or insufficient injury information in the PM, were excluded. Injuries were scored using the Injury Severity Score (ISS) and cases classified as survivable (ISS <25), potentially survivable (ISS 25–49) or non-survivable (ISS >49). Results: Of the 1796 eligible cases, 11% had injuries classified as survivable, 28% were potentially survivable, and 61% were non-survivable. Non-survivable injuries were more common among people aged 15–29 years, those sustaining transport-related injuries or multiple injuries. Non-survivable injuries were less likely to be caused by assault than injuries considered survivable or non-survivable. No differences were observed by ethnicity, sex, day of week, seasonality of the event, or distance to advanced-level hospital care. Most 'survivable' cases were deceased when found. Among those found alive, half had received either EMS or bystander care while 20% had documented delays in receiving care. Conclusion: Most prehospital injury deaths were non-survivable and most people with survivable injuries were deceased when found. Efforts to redress delays in care require attention. Learning Outcomes: The limited survivability of pre-hospital deaths emphasises the need to prioritise injury prevention and enhance appropriate bystander first-aid, timeliness of EMS care, and access to advanced-level hospital care.